Selective migration and health - Timothy J. Halliday; Michael C. Kimmitt (Institute for the Study of Labor (IZA), 2008)
Using data from the Panel Study of Income Dynamics, we investigate the impact of health on domestic migration within the United States. We find that, for men below 60 years of age, a move from the middle to the bottom of the health distribution reduces mobility by 32-40%. Non-random attrition from the panel implies that these are lower bounds. By contrast, we find evidence that, among older men, there is higher mobility at the top and bottom of the health distribution than there is in the middle. For women, we find no evidence of a relationship between their own health and mobility, although spousal health does affect the mobility of married women.
urn:nbn:de:101:1-20080421155
Keywords: J61; 330; Migration; health; selection; attrition; Binnenwanderung; Gesundheit; Schätzung; USA